FINE-STRUCTURE AND MORPHOGENESIS OF THE MICROPYLE APPARATUS IN BEES EGGS - Landim, CDC; Yabuki, A. T. (Inst Histol Embriol-conicet, 1995)
The present paper deals with the description of the formation of the micropylar apparatus in some species of Apidae bees. The features of the cells located in the anterior pole of the oocyte chamber are described at light microscopy and with SEM and TEM. The resulting micropylar region has the form of a sieved plate, slightly elevated in relationship to the oocyte surface. It is not clear if all the holes in the sieve are opened.
Keywords: BEES; MICROPYLE APPARATUS; CELLULAR PROJECTIONS; LIGHT MICROSCOPY; ELECTRON MICROSCOPY